Synthesis and Physicochemical Characterization of Anion Exchanger Based on Green Modified Bottle Gourd Shell - Dragana Z. Marković-Nikolić; Aleksandar Lj. Bojić; Saša R. Savić; Sanja M. Petrović; Dragan J. Cvetković; Milorad D. Cakić; Goran S. Nikolić (Journal of Spectroscopy)
The structural performance and biosorption behavior of a new cationic biosorbent (CALV) prepared from bottle gourd (Lagenaria vulgaris) shell (LVS) as a potentially valuable agrowaste have been established. The biosorbent with anion exchangeable function was synthesized from a modified lignocellulosic biomass (MLV) by a quaternary ammonium agent, N-(3-chloro-2-hydroxypropyl)trimethylammonium chloride. Preparation of the appropriate MLV precursor was firstly carried out by the process of alkaline pretreatment of LVS biomass using a green carbonate solution. In this way, partial delignification, removal of extractive substances, and increased porosity of the cellulose-enriched MLV biomass, as well as the activation of available cellulosic microfibrils to alkaline-cellulose have been achieved. The optimization of synthesis conditions was carried out by direct estimation of the CALV biosorption efficiency to phosphate (using ICP-OES) and nitrate (using UV-VIS) from the aqueous solutions. The structural changes of MLV precursors during green modification and the success of synthesis and biosorbent performances before and after the removal of anions from contaminated solutions have been registered and clarified by physicochemical methods, which include elemental analysis, chemical constitution, morphological characterization, and FTIR spectroscopy. In accordance with the FTIR spectroscopic analysis and isotherm studies, a structural model of the CALV biosorbent and its ion exchange mechanism are proposed.